Slow Titration of Cannabidiol Add-On in Drug-Resistant Epilepsies Can Improve Safety With Maintained Efficacy in an Open-Label Study - D'Onofrio, Gianluca; Kuchenbuch, Mathieu; Hachon-Le Camus, Caroline; Desnous, Béatrice; Staath, Véronique; Napuri, Sylvia; Ville, Dorothée; Pedespan, Jean-Michel; Lépine, Anne; Cances, Claude; de Saint-Martin, Anne; Teng, Théo; et al. (Frontiers in Neurology, 2020)
Objective: To assess adverse events (AE) and efficacy of add-on Cannabidiol (CBD) with a slower titration protocol in clinical practice in pediatric. Methods: We conducted a prospective, open-label, multi-center study in seven French reference centers for rare epilepsies. Patients had slow titration to reach a target dose of 10 mg/kg/day within at least one month, then gradually increased to a maximum dose of 20 mg/kg/day. We analyzed AE and efficacy at M1 (month 1), M2 and M6 and comparing 2 sets of subgroups: Dravet syndrome (DS) versus Lennox-Gastaut (LGS) and patients with Clobazam (CLB+) versus patients without (CLB-). Results: 125 patients were enrolled (62 LGS, 48 DS, 5 Tuberous sclerosis and 10 other etiologies). Median concomitant anti-epileptic drugs (AEDs) was 3 [25th percentile:3-75th percentile:4]. Patients received a dose of 10 [10-12], 14 [10-20] and 15.5 mg/kg/day [10-20] at M1, M2 and M6 respectively. Twenty-six patients discontinued CBD, 19 due to lack of efficacy, 2 due to AE, 4 for both and 1 had a Sudden Unexpected Death in Epilepsy. AE were reported in 61 patients (48.8%), mainly somnolence (n=26), asthenia (n=20), behavior disorders (n=16). Abnormal transaminases (≥ 3 times) were reported in 11 patients receiving both valproate and clobazam. AE were significantly higher at M2 (p=0.03) and increased with the number of AEDs (p=0.03). At M6, total seizure frequency change from baseline was -41+/-37.5% (mean+/-standard deviation) and 28 patients (37.8%) had a reduction ≥50%. AE and efficacy did not differ between DS versus LGS and CLB+ versus CLB- patients. Significance: A slower titration of CBD dose delivered better tolerance with comparable efficacy to previous trials. Concomitant CLB did not increase efficacy rates but in few cases increased AEs. This slow titration scheme should help guide clinicians prescribing CBD and allow patients to benefit from its potential efficacy.